2016
DOI: 10.1186/s40795-016-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

The synergystic effects of omega-3 fatty acids against 5-fluorouracil-induced mucosal impairment in mice

Abstract: Background: Anti-cancer pharmaceuticals frequently have adverse side effects on patients such as gastrointestinal involvement limiting their clinical applications. These effects may be controlled by nutritional interventions, however, there are few studies that have shown any mechanistic effects. In this study, we examined effects of diet enhanced with eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on 5-fluorouracil (5-FU)-induced intestinal impairment and immunity in mice. Methods: C57Bl6 mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The combined strategy not only decreased the tumor burden but also significantly reduced the associated side effects. 6,29 Various mechanisms have been hypothesized to explain the modulation of the tumor cell response to chemotherapeutic drugs by FO which includes an alteration in the expression of pro-apoptotic proteins and membrane characteristics by incorporation of n-3 PUFAs in the membrane. However, no experimental data to validate this hypothesis are available till date, which necessitates further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The combined strategy not only decreased the tumor burden but also significantly reduced the associated side effects. 6,29 Various mechanisms have been hypothesized to explain the modulation of the tumor cell response to chemotherapeutic drugs by FO which includes an alteration in the expression of pro-apoptotic proteins and membrane characteristics by incorporation of n-3 PUFAs in the membrane. However, no experimental data to validate this hypothesis are available till date, which necessitates further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo studies have described that PUFAs can reduce 5-FU-related toxicity and potentiate 5-FU anti-cancer activity though the reduction of tumor burden and DNA damage and the increase of apoptosis [131][132][133]. A recently study in rat models showed that combining PUFAs with 5-FU and irinotecan could help restore lipid stocks, thus potentially limiting 5-FU-associated side effects [134].…”
Section: Diets Rich In Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Vasudevan et al demonstrated a synergistic anti-cancer effect between EPA and a regimen of 5-fluorouracil (5-FU) and oxaliplatin in vitro and in vivo against HT29 and HCT116 CRC models [ 52 ]. Several other in vivo studies have demonstrated that O3FAs can both potentiate 5-FU anti-cancer activity (reduction of tumour burden, increased apoptosis, and DNA damage) and also reduce 5-FU-related toxicity [ 53 55 ]. In 2017, a study showed that 5-FU and irinotecan treatment can lead to impaired lipid storage in rat models, resulting in loss of O3FA in tissues.…”
Section: Preclinical Data Supporting the Anti-crc Activity Of O3fasmentioning
confidence: 99%